A Guide towards Building Effective, Metrics-Driven and Mathematical Sales Segmentation Models for an Enterprise B2B SaaS Business (Global Journal of Management and Business Research, 2020)
The paper#x2019;s goal is to help B2B SaaS companies attain two primary goals - 1. Leverage best-in-class business firmographic data for building territory segmentation models 2. Balance the models against the most effective sales metrics, and 3. Understand and optimize for territory disruption year over year due to change in the scale of business. In the paper, we build a model based on the most fundamental building blocks of any SaaS business.
Keywords: sales operations; sales strategy; analytics; territory operations; segmentation; territory carving